2018
DOI: 10.1021/acsomega.8b01282
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Photoelectric Properties of 2D Silicene/MX2 (M = Mo, W; X = S, Se) Heterostructures

Abstract: The transport and photoelectric properties of four two-dimensional (2D) silicene/MX 2 (M = Mo, W; X = S, Se) heterostructures have been investigated by employing density functional theory, nonequilibrium Green’s function, and Keldysh nonequilibrium Green’s function methods. The stabilities of silicene (SiE) are obviously improved after being placed on the MX 2 (M = Mo, W; X = S, Se) substrates. In particular, the conductivities of SiE/MX 2 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 101 publications
1
13
0
Order By: Relevance
“…As we can see from Figure 3, the strongest peak centred at 27.5 was assigned to the (002) reflection, which can be assigned to the conjugated aromatic system stacking and contributed to an interplanar spacing around 0.326 nm. [46,47] The peak centred at 13.1 corresponded to the (100) reflection and was indicative of the in-planar repeating motifs of the continuous heptazine network with a d-value of 0.675 nm in the crystal, as was reported in previous works. [46,47] A FTIR spectrum of the g-C 3 N 4 was also conducted in order to investigate the functional groups, which play a role in the application of g-C 3 N 4 .…”
Section: Characterizationsupporting
confidence: 62%
See 1 more Smart Citation
“…As we can see from Figure 3, the strongest peak centred at 27.5 was assigned to the (002) reflection, which can be assigned to the conjugated aromatic system stacking and contributed to an interplanar spacing around 0.326 nm. [46,47] The peak centred at 13.1 corresponded to the (100) reflection and was indicative of the in-planar repeating motifs of the continuous heptazine network with a d-value of 0.675 nm in the crystal, as was reported in previous works. [46,47] A FTIR spectrum of the g-C 3 N 4 was also conducted in order to investigate the functional groups, which play a role in the application of g-C 3 N 4 .…”
Section: Characterizationsupporting
confidence: 62%
“…[46,47] The peak centred at 13.1 corresponded to the (100) reflection and was indicative of the in-planar repeating motifs of the continuous heptazine network with a d-value of 0.675 nm in the crystal, as was reported in previous works. [46,47] A FTIR spectrum of the g-C 3 N 4 was also conducted in order to investigate the functional groups, which play a role in the application of g-C 3 N 4 . As depicted in Figure 4, the obvious multiple adsorption bands at 1413, 1472, 1570, and 1640 cm −1 correspond to the stretching vibration modes of the heptazine-derived rings, which is in accordance with a previous report.…”
Section: Characterizationmentioning
confidence: 56%
“…[250] Silk fibroin (SF)/graphene oxide (GO)-blended nanofibers (SF/GO-blended nanofibers) have been used to study the antibacterical efficacy against Gram-positive (S. aureus) and Gram-negative (E. coli). [251] A three-component composite made up of cobalt ferrite, silver nanoparticles, and graphene oxide synthesized and utilized to study the antibacterial activity after being combined with ciprofloxacin drug. [252] The effect of GO as antibacterial agent has been studied toward bacteria like S. mutans, [253] Escherichia coli, [230,254a-k] Pseudomonas aeruginosa, [255,254i] Staphylococcus aureus, [254c,e,f,h,i,k,256,230] Klebseilla, [256] and Bacillus subtilis.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…For instance, B‐doped graphene (BG), prepared by pyrolyzing a mixture of graphene oxide and boric acid at 900 °C under Ar atmosphere, was demonstrated to be catalytically selective for HCOO − production, exhibiting a FE HCOO − of 66% at an applied potential of −1.4 V versus SCE . Recent theoretical calculations by Tang et al further revealed the ability of Boron nitride nanoribbons (BNNRs) to generate C 2 products such as C 2 H 4 and C 2 H 5 OH as a result of B edge atoms and C dopants that would serve as active sites for CO 2 RR . Interestingly, B‐doping is widely used to functionalize inert diamond catalysts (to generate boron‐doped diamond, BDD).…”
Section: Active Sites In Carbon‐based Catalystsmentioning
confidence: 99%